The Role of Religiosity and Trust in Government in Student Tax Morale Perceptions: (Empirical Study of Students at the University of Al-Qur'an Science) - M. Trihudiyatmanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
Objective - This study aims to demonstrate the influence of religiosity and trust in government on the perceptions of tax morality among Management students at the Al-Quran Science University of Central Java in Wonosobo. Method - The sample in this study consisted of 182 Management students who had taken behavioral management courses, selected using a purposive sampling method. Data were collected through an online questionnaire (Google Form) distributed to sixth- and eighth-semester Management students. The results were analyzed using multiple linear regression analysis (MLA), followed by statistical tests, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, and hypothesis testing using t-tests, f-tests, and coefficients of determination. Results - The results indicate that religiosity has a positive effect on management students' perceptions of tax morality, as evidenced by a calculated t-value of 2.096 > t-table 1.973 with a significance value of 0.038 < 0.05. Trust in government has a positive effect on management students' perceptions of tax morale, as evidenced by a calculated t-value of 13.618 > t-table 1.973, with a significance value of 0.000 < 0.05. Implications – This study aims to identify factors influencing perceptions of tax morale among students, and it is also hoped that this research can provide input, particularly for management majors, to continuously improve the quality of learning and produce graduates with high levels of tax morale.